2011
DOI: 10.1590/s1808-86942011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison: real and simulated ear insertion gain

Abstract: The development of hearing aid (HA) software programming does not replace the analysis of real ears with probe microphones. Aim:To compare simulated insertion gain in HA software programming and real ear insertion gain.Method: A prospective study of 62 patients (aged from 29 to 93 years; 30 male and 32 female). All patients presented unilateral (n=14) or bilateral (n=48) and mild to profound sensorineural hearing impairment. 110 ears assessed. Data was gathered from medical records and the insertion gain was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In the analysis by frequency bands ( Table 2), it can be noted that the frequencies of 500, 1000, 2000, and 4000 Hz showed higher values at the LM, which may indicate that the predominant noise in the working environment is within these frequency bands. Regarding the intensities verified by the PM at each of the frequencies (Table 2), we should mention that the depth of the probe insertion can interfere with the results due to the presence of the standing waves, particularly for higher frequencies (19) , which could change the level of sound pressure measured in real-ear measurements (21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis by frequency bands ( Table 2), it can be noted that the frequencies of 500, 1000, 2000, and 4000 Hz showed higher values at the LM, which may indicate that the predominant noise in the working environment is within these frequency bands. Regarding the intensities verified by the PM at each of the frequencies (Table 2), we should mention that the depth of the probe insertion can interfere with the results due to the presence of the standing waves, particularly for higher frequencies (19) , which could change the level of sound pressure measured in real-ear measurements (21) .…”
Section: Discussionmentioning
confidence: 99%
“…At one end, the microphone is connected to the silicone probe, which is 58 mm long. Nevertheless, only 28 mm was inserted into the EAM of the participants, value adopted by the geometric method (19) , thereby ensuring that the probe would not be obstructed by the HP, which was 25 mm long. To assist with inserting the probe on the EAM, an otoscope and a pre-molding flashlight were used.…”
Section: Methodsmentioning
confidence: 99%
“…The prescriptive gain displayed in the manufacturer's software may be quite different in real ear. Despite the increasing sophistication on hearing aid programming software, simulation data do not replace the probe microphone measurement (22) . Possible complaints about the hearing aid acceptance may be related to the fact that adjustments were made based only on simulated data and not on probe microphone measures.…”
Section: Discussionmentioning
confidence: 99%
“…Aarts and Caffee investigated the clinical accuracy of measured and manufacturer-predicted real-ear aided re-sponse (REAR) in adults and reported that these values differed significantly from the predicted response values [9]. Aazh et al (2012) [10] and Campos et al (2011) [11] investigated the fitting accuracy of Real-Ear Insertion Gain (REIG) with the initial fitting of hearing aids in 30 and 62 adults, respectively. They reported that the target insertion gain could rarely be achieved through the first fit.…”
Section: Introductionmentioning
confidence: 99%